Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline pada Materi Komunikasi Telepon dalam Bahasa Inggris di SMK IPIEMS Surabaya - Wardani, Kamelia Kusuma; Puspasari, Durinta (UNDIKMA, 2022)
This study aims to analyze the development process as well as the response of students to interactive media in the field of education based on Articulate Storyline on the material of Telephone Communication in English. This research method uses research and development with the ADDIE model. The subject of the research trial was a group of 20 students. X OTKP 1 SMK IPIEMS Surabaya. The data collection instrument used expert validation sheets and student response questionnaires. The data analysis technique of this research used descriptive analysis. The results of this study indicate that: 1) the process of developing interactive media for teaching and learning based on Articulate Storyline is ongoing with Telephone Communication in English class X OTKP 1 SMK IPIEMS Surabaya carried out through four steps, namely Analysis, Design, Development, and Implementation; 2) learning media is categorized as feasible based on the average validation value obtained from the three validators, which is 97%; 3) the results of student responses that obtained an average value of 92%. Therefore, it can be concluded that the interactive learning media based on Articulate Storyline on Telephone Communication in English is very feasible to be used for learning media facilities at the learning and teaching stages at SMK IPIEMS Surabaya and getting a positive response in the